Treatment Failure in Osteoradionecrosis Involving the Mandible Following Enblock Resection of the Affected Bone: A Case Report (Tanzania Medical Journal, 2008)
Osteoradionecrosis (ORN) of the jaws is a relatively common side effect of radiotherapy of head and neck tumours. It is a chronic condition that progresses slowly and does not tend to heal spontaneously. Irradiation brings about histological changes in hard and soft tissues, such as loss of ostoecytes, absence of osteogenic precussor cells, replacement of bone marrow by loose connective tissues and reduced expression of collagens and bone morphogenic protein by fibroblasts. Secondary lesions of these hypoxic tissues may then lead to an infection of the previously weakened bone and soft tissue and to development of a chronic, non-healing wound. Resection of bone without viable cells that remain around the area of resection will not facilitate revitalization. A case is presented of 35-year-old female with ORN of the mandible who presented with failure of wound healing following enblock resection of the affected part of bone. The possible causes of treatment failure and their management are discussed. Tanzania Medical Journal Vol. 23 (1) 2008: pp. 34-37